Renúncias de receita de ICMS destinadas ao setor minerário no Estado do Pará - CONCEIÇÃO, Luan Pedro Lima da (Universidade Federal do Pará, 2018)
The present work is inserted, primarily, in the Tax and Financial legal areas and has as its central purpose the legal validity analysis of revenue waivers relating to the Tax on Transations Relating to the Movement of Goods and the Provision of Interstate and Inter-municipal Transport Services and Communication (ICMS) destined to the extractive mining sector in the State of Pará. For this purpose, the work is initiated through an eminently propaedeutic stage in which fundamental legal definitions for the development of the research are addressed, and the structural legal basis of the thesis is delimited. Are analyzed, also, the revenue waivers through the Theory of Law as prizes or positive sanctions in a legal promotional context. In the second stage of the work, the current desonerative policy for the State of Pará mining sector is exposed so that, in the third stage, the main financial and tax charges on mining are presented. In the fourth stage of the work, one enters into the legal analysis of the revenue waivers, wondering about the validity if the mentioned exemptions. In the last stage of the research, the exemptions are analyzed under the approaches of legitimacy and economicity, moving towards a finalistic approach both environmental and federative. To briefly summarise, the present work aims to inquire about the validity of such revenue waivers in a context in which the Public Authority assumed for itself the responsibility for the implementation of fundamental rights, with taxation being its main source of funds for this purpose.